ABC7 Consensus: Assessment by a German Group of Experts - Ditsch, Nina; Untch, Michael; Fasching, Peter; Busch, Steffi; Ettl, Johannes; Haidinger, Renate; Jackisch, Christian; Lüftner, Diana; Müller, Lothar; Müller, Volkmar; Ruckhäberle, Eugen; Schumacher-Wulf, Eva; et al. (Breast Care, 2024)
Background: The "International Consensus Conference for Advanced Breast Cancer"was initiated more than 10 years ago. The rationale was to standardize treatment of advanced breast cancer (ABC) based on available evidence and to ensure that all ABC patients worldwide receive adequate treatment and access to new therapies. Topics of ABC7: The 7th International Consensus Conference for ABC (ABC7) took place from November 9 to 11, 2023 - as in previous years in Lisbon/Portugal. ABC7 focused not only on metastatic disease but also on locally advanced and inflammatory breast cancer. Special topics were the management of oligometastatic disease, leptomeningeal disease, brain metastases, and pregnant women with ABC. Due to the current situation worldwide, there was a special interest to patients living in conflict zones. As in previous years, patient advocates from around the world were integrated into the ABC conference and had a major input to the consensus. Rationale for the Manuscript: A German breast cancer expert panel comments on the voting results of the ABC7 panelists regarding their relevance for routine clinical practice in Germany. As with previous meetings, the ABC7 votes focused on modified or new statements. Regarding the statements not modified for the ABC7 consensus, they are discussed in the published manuscript from 2021 in which the German experts commented on the ABC6 consensus. The German comments are always based on the current recommendations of the "Breast Committee"of the Gynecological Oncology Working Group (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO Mamma).
CRIS-Team Scopus Importer:2024-05-03
Keywords: ADCs; Advanced breast cancer and pregnancy; Brain metastases; Leptomeningeal disease; Oligometastatic disease; Systemic therapy